Parents who misuse drugs and alcohol : effective interventions in social work and child protection - Forrester, Donald; Harwin, Judith; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
This book presents original research outlining the key elements in responding to parental misuse of drugs and alcohol. Offers a definition of "misuse" and "addiction" and the factors that influence the nature of misuse or addictionReviews extensively the nature and impact of parental substance misuse on children and families using the latest evidenceExplores how research and theories might help inform professionals or non-professionals assessing families affected by parents who misuse drugs or alcoholProvides an in-depth discussion of Motivational Interviewing, including a critical discussion o.
What is "substance misuse"? -- The impact of parental substance misuse on child welfare -- Parental substance misuse and children's services -- The social worker assessments -- What happened to the children and their parents? -- Assessment chapter -- What works in engaging parents who misuse drugs or alcohol? -- What works : substance misuse treatment and evidence based social work -- Motivational interviewing and effective work with families in which parents misuse drugs and/or alcohol.
Includes bibliographical references and index.
Print version record.
Keywords: Parents -- Substance use -- Great Britain; Parents -- Alcohol use -- Great Britain; Child welfare -- Great Britain; Children of drug abusers -- Services for -- Great Britain; Children of alcoholics -- Services for -- Great Britain; Child welfare -- Great Britain; Children of drug abusers -- Services for -- Great Britain; Parents -- Alcohol use -- Great Britain; Parents -- Substance use -- Great Britain; Children of alcoholics -- Services for -- Great Britain; Electronic books